2020
DOI: 10.1109/access.2020.2986810
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and End-to-End Deep Learning for Monitoring Driver Distractions From Physiological and Visual Signals

Abstract: It is only a matter of time until autonomous vehicles become ubiquitous; however, human driving supervision will remain a necessity for decades. To assess the driver's ability to take control over the vehicle in critical scenarios, driver distractions can be monitored using wearable sensors or sensors that are embedded in the vehicle, such as video cameras. The types of driving distractions that can be sensed with various sensors is an open research question that this study attempts to answer. This study compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…DL architectures for signal processing have not yet realized any outstanding breakthrough, and designing them remains challenging, especially for problems with limited data for training. The main aim of the experiments was to compare ten end-to-end DL architectures (see Section 3.1 ): Fully convolutional network (FCN) [ 44 ], Residual network (Resnet) [ 45 ], Multi layer perceptron (MLP) [ 44 ], Encoder [ 46 ], Time convolutional neural network (Time-CNN) [ 47 ], Multichannel deep convolutional neural network (MCDCNN) [ 47 ], Spectrotemporal residual network (Stresnet) [ 48 ], Convolutional neural network with long-short term memory (CNN-LSTM) [ 5 ], Multi layer perceptron with long-short term memory (MLP-LSTM), and InceptionTime [ 49 ]. …”
Section: Methodsmentioning
confidence: 99%
“…DL architectures for signal processing have not yet realized any outstanding breakthrough, and designing them remains challenging, especially for problems with limited data for training. The main aim of the experiments was to compare ten end-to-end DL architectures (see Section 3.1 ): Fully convolutional network (FCN) [ 44 ], Residual network (Resnet) [ 45 ], Multi layer perceptron (MLP) [ 44 ], Encoder [ 46 ], Time convolutional neural network (Time-CNN) [ 47 ], Multichannel deep convolutional neural network (MCDCNN) [ 47 ], Spectrotemporal residual network (Stresnet) [ 48 ], Convolutional neural network with long-short term memory (CNN-LSTM) [ 5 ], Multi layer perceptron with long-short term memory (MLP-LSTM), and InceptionTime [ 49 ]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, Ramírez et al [34] and Takemura et al [35] proposed a method that uses a head mounted sensors. A few researches have been conducted recently for driver's attention detection by integrating various approaches, for example, combining driver's physiological signals and visual signal [36], driver's physiological signals and driving contexts [37] or driver's visual cues and driving patterns [38].…”
Section: Related Workmentioning
confidence: 99%
“…The results of this study are presented in Preprint C.1.1 (Update 02.08.2020: This is now published in IEEE Access. See [56]).…”
Section: Automatic Mental State Analysismentioning
confidence: 99%
“…4 This study is described in detail in Preprint C.1.1 (Update 02.08.2020: This is now published in IEEE Access. See [56]). It was found that the intensities of AU25-LipsPart produced the most informative feature for recognising cognitive distraction.…”
Section: Driver Distraction and Facial Activitymentioning
confidence: 99%
See 1 more Smart Citation